Custodiol cardioplegia solution compared to cold blood cardioplegia in pediatric cardiac surgery: a single-institution experience. (May 2020) - Bibevski, Steven; Mendoza, Laura; Ruzmetov, Mark; Tayon, Kevin; Alkon, Jaime; Vandale, Breanna; Scholl, Frank
Objective: Custodiol is an intracellular, crystalloid cardioplegia solution that is a single-dose alternative to multi-dose cold blood cardioplegia; however, there is scarce data regarding its use in infants and children. The objective of this study was to compare its impact on myocardial function in infants. Methods: Single-center retrospective review including 132 patients <12 months old undergoing biventricular repair. There were 106 patients who received single-dose Custodiol and 27 patients who received multi-dose blood cardioplegia. Demographic and echocardiographic data were compared between the two groups. Results: Patients receiving Custodiol were slightly younger (100 ± 62 days) and lower weight (4.7 ± 1.3 kg) compared to 152 ± 86 days and 5.2 ± 1.3 kg for blood cardioplegia (p < 0.05). The Society of Thoracic Surgeons/European Association for Cardio-Thoracic Surgery Congenital Heart Surgery score was similar between both groups. Average cardiopulmonary bypass time was similar between both groups (Custodiol 93 ± 54 minutes vs. blood 81 ± 44 minutes, p = 0.46) as was aortic cross-clamp time (Custodiol 58 ± 33 minutes vs. cold blood 53 ± 33 minutes, p = 0.62). Pre-operative left ventricular ejection fraction was similar for blood 73 ± 8% versus Custodiol 70 ± 9%, p = 0.21. There was also no intergroup difference in left ventricular ejection fraction 24 hours post op (blood 64 ± 9% vs. Custodiol 65 ± 12%, p = 0.53) or at discharge (blood 66 ± 10% vs. Custodiol 66 ± 11%, p = 0.95). The pre-operative right ventricle function by fractional area change was also similar in blood cardioplegia (46 ± 13%) versus Custodiol (48 ± 9%, p = 0.38) and showed similar drops in parameters in the two groups 24 hours after surgery and at discharge. Conclusion: Single-dose Custodiol is as safe as blood cardioplegia for myocardial protection in congenital cardiac surgery for the cross-clamp times evaluated in this study. Evaluation at longer cross-clamp times would be helpful to determine if there is a greater benefit to single-dose Custodiol versus more repeated doses of blood cardioplegia for longer cross-clamp times.